Th e Relation between Economic Balance, Stratification and Solidarity in the Islamic Society - Hossein Namazi; Alireza Lashkari (Islām va ̒ulūm-i ijtimā̒ī)
Social justice, based on its various principles such as ontological and anthropological principles, has complex dimensions. While reviewed from different perspectives, it becomes even more complex. One of the defining principles for illustrating social justice is the type of approach to individual and society. According to the individualistic approach balance has not much scope in social justice theory for and Social Justice is followed in the form of "poverty removal".  But according to Shahid Sadr and Shahid Motahari’s views, as they believe in individualism and socialism, the balance can contribute to the explanation of social justice. According to the second approach, inequality is defined in terms of the imbalance and at odds with social justice. The individualistic view of social justice is solely defined by means of poverty removal and in consistence with inequality.  While explaining the attitude toward "individualism and socialism" from balance perspective, the author of the of the present paper takes into consideration that understanding social justice in Islamic system is possible when the dimensions of society which is associated with the structure of society is deeply explored. So he deals with the issue of stratification and social cohesion in the knowledge of sociology and investigates the relation between social justice and inequality in Islam.  The result is that Islam seeks dignity of people and public consent through establishment of justice in satisfaction. By preventing the concentration of wealth in the hands of a few, Islam provides individual people of society with equal access to opportunities and maintains their dignity and consent.